Biochar Enhances Soil–Plant–Microbe Interactions in Saline Soil - Khan, Tazeen Fatima; Anik, Md Golam Sarwar; Hossain, Sonia (Research in Ecology, 2025)
A controlled pot experiment was carried out to examine the interactive effects of salinity stress and biochar on the growth, nutrient uptake, and soil microbial dynamics of Lablab purpureus. Results showed that wheat husk biochar significantly (p < 0.05) enhanced plant growth parameters compared to controls. Plant height increased by c. 53%, root length by 37%, fresh weight by 125%, and dry weight by 92% in wheat husk char treated soil under non-saline conditions. Wheat husk char also significantly increased pod number and node count per plant by c. 42% and 28% respectively. Nutrient analysis revealed higher concentrations of N ( 6%), P ( 0.3%), and K ( 2%) in wheat husk biochar treatments, while salinity reduced nutrient uptake across all treatments. Although the number of flowers increased by c. 75%, the difference was not statistically significant. Although 16S rRNA gene copy numbers did not show significant changes in biochar treatments, enhanced microbial function indicated improved nutrient cycling and ecosystem functionality. Overall, the findings suggest that biochar can mitigate the adverse effects of salinity by improving plant physiological traits and stimulating microbial activity. This highlights biochar’s potential as an ecological tool for sustainable agriculture, biodiversity enhancement, and ecosystem restoration in saline affected areas.